ADHD – A GLOBAL CHALLENGE. ARE WE CLOSER TO THE IDEAL THERAPY? - Karina Grzesik,; Katarzyna Pilarczyk,; Aleksandra Rabęda,; Antoni Gawor,; Natalia Klepacz, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and objective: The treatment of ADHD remains a topic of global discussion among researchers and clinicians. Stimulant medications are the primary therapy, but concerns about side effects, addiction, and misuse have led to growing interest in alternative methods, such as behavioral therapy, cognitive training, neurofeedback, and dietary interventions. This review aims to compile data on ADHD treatment and assess whether alternative therapies can replace stimulants.Brief description of the state of knowledge: Numerous studies describe individual therapeutic methods, but a lack of definitive conclusions persists due to uncertainties and isolated evaluations. More comparative research and studies on combined treatments are needed to determine the most effective approaches. Particularly, there is a shortage of studies on integrating pharmacological and alternative therapies, highlighting the need for future research.Methods: A literature review was conducted using PubMed and Google Scholar with search terms like “ADHD - diagnostic criteria and symptoms”, “Stimulant medications in the treatment of ADHD”, “Alternative treatment methods for ADHD”, “Dietary treatment and supplementation in ADHD”. Articles published within the last five years were prioritized.Conclusions: Stimulants remain the most effective ADHD treatment but are associated with side effects such as sleep disturbances, appetite loss, and addiction concerns. In response, alternative therapies are gaining popularity, though evidence of their standalone effectiveness is limited. Further comparative and combination therapy studies are necessary to develop a more comprehensive treatment approach that optimizes symptom reduction while minimizing risks. At present, stimulant medications are a safe first-line treatment with proven efficacy.